2019
DOI: 10.1111/1744-9987.12794
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Mean Platelet Volume in Predicting Cardiac Mechanics Parameters and Carotid‐Intima Media Thickness in Children With End‐Stage Renal Disease and Comparison With Healthy Children

Abstract: Cardiovascular disease (CVD) is the major cause of death in children with ESRD. Echocardiography and Doppler ultrasound are useful devices for diagnosing cardiovascular abnormalities in such patients. However, they are expensive, difficult to perform as a routine, and not available in many centers. Therefore, finding a more accessible and inexpensive method for CVD evaluation biomarkers is needed. The aim of this study was to evaluate the relationship between mean platelet volume (MPV) as a routine hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Similar result observed in Assiri A S et al study where 37.7% study subjects of ACS groups than control. 11 In 21,26 The study reveals that the mean (±SD) value of total platelet count was lower in cases than controls without any significant statistical difference (p -0.239). Total platelet count was 258±44 X 10 17,22,23,24,25,14,8,18,11 In our study, we found no significant difference (p -0.239) in mean platelet count between two groups.…”
Section: Resultsmentioning
confidence: 85%
“…Similar result observed in Assiri A S et al study where 37.7% study subjects of ACS groups than control. 11 In 21,26 The study reveals that the mean (±SD) value of total platelet count was lower in cases than controls without any significant statistical difference (p -0.239). Total platelet count was 258±44 X 10 17,22,23,24,25,14,8,18,11 In our study, we found no significant difference (p -0.239) in mean platelet count between two groups.…”
Section: Resultsmentioning
confidence: 85%
“…The role of MPV in LV hypertrophy development is controversial. Due to the recent study MPV can be an early predictor of LV hypertrophy development [14]. PLR is the known systemic inflammatory marker, that is associated with AF paroxysm and progression [15].…”
Section: Discussionmentioning
confidence: 99%
“…14 Routine laboratory investigations are broadly implemented in clinical settings and are of great clinical importance in predicting the diagnosis and progression of many diseases, such as anemia, [15][16][17] infectious diseases, 18,19 tumors, 20,21 and cardiovascular diseases. [22][23][24] Routine blood investigations are inexpensive and easily conducted. Routine blood parameters such as platelet count, white blood cell )WBC( count, and neutrophilto-lymphocyte ratio )NLR( have been widely studied in clinical practice 25 as markers of many pathological conditions, such as inflammation.…”
Section: Discussionmentioning
confidence: 99%